PENGARUH RENDAM KAKI DENGAN AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI KELURAHAN GAHARU - Lasma Rina Efrina Sinurat; Siska Dwi Ningsih; Henny Syapitri (Jurnal Online Keperawatan Indonesia, 2020)
Hypertension is an increase in diastolic and systolic blood pressure that is intermittent or persistent. The national prevalence of hypertension at the age of 55-64 years is 45.9%, those aged 65 years and over are 57.6%, and those aged 75 years and over are 63.8%. One of the complementary alternative therapies in hypertensive patients is doing "hydrotherapy" which can lower blood pressure if done regularly. The treatment is soaking the feet in warm water. This study aims to determine the effect of foot soak with warm water on reducing blood pressure in hypertensive elderly in Gaharu Village. This type of research is a quasi-experimental design with a one-group pre and post test design. The sampling technique used in this study was purposive sampling with a total sample of 40 respondents. Collecting data in this study using observation sheets. From the results of the paired t test showed that there was a significant effect before and after foot bath therapy with warm water, the p-value = 0.000 (<0.05). It is recommended for elderly people with hypertension to control their blood pressure to health services and routinely perform complementary therapy of foot soaks with warm water to lower blood pressure.